Conjugated polymer dots for biocompatible siRNA delivery. (28th August 2019) - Wang, Fei; Chen, Haobin; Liu, Zhihe; Mi, Feixue; Fang, Xiaofeng; Liu, Jie; Wang, Mingxue; Lo, Pik Kwan; Li, Qiong
Abstract : The constructed nanoplatform not only retained the outstanding fluorescence properties and biocompatibility but also enhanced delivery efficiency of siRNA. Abstract : Small interfering RNA (siRNA) that mediates target gene silencing through RNA interference (RNAi) has attracted increasing interest in exploring gene functions as well as treating a variety of diseases. However, the inefficient delivery of the unstable and negatively charged siRNA into cells restricts the progress of the RNAi-based therapeutics. In this work, we describe the development of a nanoplatform based on conjugated polymer dots (Pdots) for efficient siRNA delivery. The cationic lipid G0C14 was introduced in the Pdots for siRNA complexing. The G0C14-containing polymer dots (G-Pdots) not only retained the outstanding fluorescence properties but also enhanced cellular uptake of siRNA. The positively charged G0C14 was able to interact with the negatively charged siRNA via electrostatic interactions, while the G-Pdot/siRNA complexes still remained negatively charged. A prominent property of this nanoplatform was the low cytotoxicity as compared to the commercial agent Lipofectamine, while the gene silencing efficiency was comparable. Our results indicate that biocompatible G-Pdots represent a promising platform for imaging-guided siRNA delivery.